Come together. - Hogge, Becky (New Statesman, 2008)
In this article the author discusses the development open-source software, such as the Linux operating system and the Mozilla Firefox web browser. She praises the enthusiasm that open-source designers bring to their endeavors. She describes events at the 2008 Free and Open-Source Software Developers' European Meeting in Brussels, Belgium.